2020
DOI: 10.34172/ijhpm.2020.96
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Burden Due to Registrations for Quality Monitoring and Improvement in Hospitals: A Mixed Methods Study

Abstract: Background: Quality indicators are registered to monitor and improve the quality of care. However, the number and effectiveness of quality indicators is under debate, and may influence the joy in work of physicians and nurses. Empirical data on the nature and consequences of the registration burden are lacking. The aim of this study was to identify and explore healthcare professionals’ perceived burden due to quality registrations in hospitals, and the effect of this burden on their joy in work. Methods: A mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 47 publications
2
37
1
1
Order By: Relevance
“…Another outcome scarcely measured is staff satisfaction; we only identified one study [ 127 ]. A growing body of literature outlines the staff’s fundamental role in healthcare [ 133 , 134 , 135 ], highlighting the need for analytical attention and technological solutions focused on minimizing the burden experienced by physicians and nurses [ 134 ]. The findings imply that most intervention studies still focus on efficiency improvement in a department rather than taking a holistic perspective to optimize the outcomes across the entire patient journey process.…”
Section: Discussionmentioning
confidence: 99%
“…Another outcome scarcely measured is staff satisfaction; we only identified one study [ 127 ]. A growing body of literature outlines the staff’s fundamental role in healthcare [ 133 , 134 , 135 ], highlighting the need for analytical attention and technological solutions focused on minimizing the burden experienced by physicians and nurses [ 134 ]. The findings imply that most intervention studies still focus on efficiency improvement in a department rather than taking a holistic perspective to optimize the outcomes across the entire patient journey process.…”
Section: Discussionmentioning
confidence: 99%
“…This is realistic because professionals understand that some administration is necessary. For instance, a study in Dutch hospitals found that only 36% of quality registrations were perceived as useful for everyday practice (Zegers et al, 2020). However, we also need to prevent useful administrative tasks from being lost in blunt eradication exercises.…”
Section: Three Resulting Reflections On Reducing Ac In Ltcmentioning
confidence: 99%
“…Yet another explanation for the stability of autonomous motivation may be that EHRs have a variety of motivation-relevant effects beside the changes in work characteristics analysed in the current paper. On the one hand, the EHR supports healthcare workers in achieving their work-related goals and values, but on the other hand the administrative burden resulting from an EHR may impair autonomous motivation [ 14 , 20 , 61 , 62 ]. More specifically, the instrumental value of the EHR is likely to contribute to healthcare workers’ sense of identified regulation.…”
Section: Discussionmentioning
confidence: 99%